Specific human antibody responses to Aedes aegypti and Aedes polynesiensis saliva: A new epidemiological tool to assess human exposure to disease vectors in the Pacific. - Françoise Mathieu-Daudé; Aurore Claverie; Catherine Plichart; Denis Boulanger; Fingani A Mphande; Hervé C Bossin (Public Library of Science (PLoS), 2018)
BACKGROUND:Aedes mosquitoes severely affect the health and wellbeing of human populations by transmitting infectious diseases. In French Polynesia, Aedes aegypti is the main vector of dengue, chikungunya and Zika, and Aedes polynesiensis the primary vector of Bancroftian filariasis and a secondary vector of arboviruses. Tools for assessing the risk of disease transmission or for measuring the efficacy of vector control programmes are scarce. A promising approach to quantify the human-vector contact relies on the detection and the quantification of antibodies directed against mosquito salivary proteins. METHODOLOGY/PRINCIPAL FINDINGS:An ELISA test was developed to detect and quantify the presence of immunoglobulin G (IgG) directed against proteins from salivary gland extracts (SGE) of Ae. aegypti and Ae. polynesiensis in human populations exposed to either species, through a cross-sectional study. In Tahiti and Moorea islands where Ae. aegypti and Ae. polynesiensis are present, the test revealed that 98% and 68% of individuals have developed IgG directed against Ae. aegypti and Ae. polynesiensis SGE, respectively. By comparison, ELISA tests conducted on a cohort of people from metropolitan France, not exposed to these Aedes mosquitoes, indicated that 97% of individuals had no IgG directed against SGE of either mosquito species. The analysis of additional cohorts representing different entomological Aedes contexts showed no ELISA IgG cross-reactivity between Ae. aegypti and Ae. polynesiensis SGE. CONCLUSIONS/SIGNIFICANCE:The IgG response to salivary gland extracts seems to be a valid and specific biomarker of human exposure to the bites of Ae. aegypti and Ae. polynesiensis. This new immuno-epidemiological tool will enhance our understanding of people exposure to mosquito bites, facilitate the identification of areas where disease transmission risk is high and permit to evaluate the efficacy of novel vector control strategies in Pacific islands and other tropical settings.